2019
DOI: 10.1515/biol-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heavy Metals and Microbiological Contamination of Selected herbals from Palestine

Abstract: BackgroundHerbal medicine is widely used for the prevention and treatment of diseases worldwide including Palestine and may require long term usage. The level of some heavy metals and microbial contaminants in some of these medicinal plants consumed by Palestinians were studied in order to evaluate their quality.MethodologyThe level of metals including: Zinc, Cadmium, Lead and Copper were quantified by Atomic absorption spectroscopy (AAS). Moreover, the bacterial and fungal contaminations were tested for some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Both iron drugs and food supplements were collected from community pharmacies, where these items are usually stored under suitable storage conditions. In our previous study on herbals, the results showed significant contamination of the tested herbals; this contamination was primarily attributed to improper storage by herbal traditional shops (Abualhasan et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Both iron drugs and food supplements were collected from community pharmacies, where these items are usually stored under suitable storage conditions. In our previous study on herbals, the results showed significant contamination of the tested herbals; this contamination was primarily attributed to improper storage by herbal traditional shops (Abualhasan et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
“…The results showed that many of the sold brand do not comply with the set international standard which may cause health hazards. are newly established, and the rules set are still unsatisfactorily implemented (Abualhasan et al, 2019), (Palestinian Ministry of Health, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another study about assessment of heavy metal contamination in roadside surface soil and vegetation from the West Bank conducted by Swaileh, et al (2004), indicate that roadside contamination with heavy metals was obvious by the significant negative correlations between concentrations of metals in soil and plant samples and distance from road edge. Previous studies had reported some high levels of heavy metals concentration in other places surrounding Jericho (Abualhasan, et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…There are many herbs that studies have indicated to be effective as a treatment for diabetes, such as Ferula assafoetida, Annona squamosal, Zingiber officinale, Gymnema But it should be noted that many of the herbal mixtures used to treat diseases that are sold in local stores and markets are contaminated with many sources of danger, such as Mycotoxigenic Fungi and Mycotoxins (Abed et al, 2020 ;Ikeagwulonu et al, 2020), As well as bacteria and heavy metals (Zamir et al, 2015;Abualhasan et al, 2019). The aim of the current study is to detect the presence of fungal contamination and mycotoxins in some of selected antidiabetic herbs mixtures are widely spread among Iraqis in Diyala Governorate population.…”
Section: Introductionmentioning
confidence: 99%